MODERN METHODS OF INCREASING LABOR EFFICIENCY IN ORGANIZATIONS THROUGH ENHANCING HUMAN DIGNITY - Beshimov Hamidjon Sayidovich (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to explore how enterprises, organizations, and institutions—both public and private—manage human resources to achieve greater efficiency and cost-effectiveness while preserving human dignity and enhancing employee potential. Method: The research employs a qualitative analytical approach, drawing from organizational management theories and case studies of enterprises with active primary trade unions to assess their impact on employee performance and workplace conditions. Results: The findings indicate that organizations which prioritize human-centered management practices and establish primary trade unions experience improved legal awareness among employees, enhanced socio-economic welfare, and stronger organizational cohesion. These factors collectively contribute to a more efficient, productive, and positive organizational environment. Novelty: This article offers an integrative perspective linking human dignity, labor relations, and organizational efficiency, emphasizing that sustainable productivity stems not merely from economic incentives but from institutional respect for employees’ rights, participation, and collective representation.